2015
DOI: 10.1016/j.chemgeo.2015.07.023
|View full text |Cite
|
Sign up to set email alerts
|

Applications and limitations of U–Th disequilibria systematics for determining ages of carbonate alteration minerals in peridotite

Abstract: 238 U-234 U-230 Th dating was conducted on carbonate alteration minerals in the peridotite layer of the Samail Ophiolite, Sultanate of Oman, in order to assess the applicability of U-series dating techniques to these types of Quaternary terrestrial carbonates and also to further constrain natural rates of carbonation of the peridotite. Due to their low U concentrations and relatively high Th/U ratios, Samail carbonates are challenging to date with the 230 Th technique because of the sensitivity of ages to corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…Mervine et al. (2015) confirmed these quaternary formation ages with U‐series disequilibrium dating. Radiocarbon in magnesium carbonates can also be used to calculate carbonation rates (Oskierski et al., 2013) and tracing atmospheric carbon sources (Power et al., 2019).…”
Section: Absolute Age Dating Of Magnesium Carbonate Formationmentioning
confidence: 69%
See 3 more Smart Citations
“…Mervine et al. (2015) confirmed these quaternary formation ages with U‐series disequilibrium dating. Radiocarbon in magnesium carbonates can also be used to calculate carbonation rates (Oskierski et al., 2013) and tracing atmospheric carbon sources (Power et al., 2019).…”
Section: Absolute Age Dating Of Magnesium Carbonate Formationmentioning
confidence: 69%
“…Such putative antiquity was contradicted by the discovery of magnesite containing live 14 C and dates spanning ∼8-45 Ka (e.g., Kelemen & Matter, 2008;Kelemen et al, 2011;Mervine et al, 2014Mervine et al, , 2015. Mervine et al (2015) confirmed these quaternary formation ages with U-series disequilibrium dating. Radiocarbon in magnesium carbonates can also be used to calculate carbonation rates (Oskierski et al, 2013) and tracing atmospheric carbon sources (Power et al, 2019).…”
Section: Young Veins In Old Ultramafic Rocksmentioning
confidence: 99%
See 2 more Smart Citations
“…Other work applied 14 C and U‐series to more than 40 samples from peridotite hosted travertine deposits and carbonate veins from across the ophiolite, finding that vein deposition occurred in many locations over the past ~350 ky, especially the past ~50 ky, related to Quaternary groundwater cycling (Clark & Fontes, 1990; Kelemen et al, 2011; Kelemen & Matter, 2008; Mervine et al, 2014). Though a large number of peridotite‐hosted carbonate veins formed in the Quaternary, some veins were too old for 14 C and U‐series (Mervine et al, 2015), indicating a more ancient history that has yet to be constrained. The present study investigates the timing of alteration in a ‘fossil' carbonate‐veined peridotite system in Wadi Fins, Oman.…”
Section: Introductionmentioning
confidence: 99%